'Jumping to conclusions' data-gathering bias in psychosis and other psychiatric disorders — Two meta-analyses of comparisons between patients and healthy individuals. (June 2016) - So, Suzanne Ho-wai; Siu, Nicolson Yat-fan; Wong, Hau-lam; Chan, Wai; Garety, Philippa Anne
Abstract: There has been an increase in attention to studying shared mechanisms underlying psychiatric disorders. The 'Jumping to conclusions' (JTC 1 ) bias, a tendency to make decisions with certainty based on insufficient information, has been reported in patients with psychosis, and process-based treatment protocols targeting this bias have recently been developed. This review aimed to investigate to what extent the JTC bias, measured by various tasks, is associated with psychotic disorders and other psychiatric disorders using a meta-analytic approach. We examined 6864 articles published between 1990 and 2015, and meta-analysed 46 studies. The first meta-analysis included 40 effect sizes comparing patients with schizophrenia spectrum or other psychotic disorders and healthy controls. There was a hastier data-gathering style in patients with psychosis than healthy individuals, with a moderate aggregated effect size. The second meta-analysis included 18 effect sizes comparing patients with non-psychotic disorders and healthy controls. There was marked heterogeneity in effect sizes and evidence for publication bias. After removal of outliers, the aggregated effect size for JTC was not statistically significant. A planned subgroup analysis showed no significant effect of JTC in depression. Other diagnostic subgroups yielded small non-significant results. Therefore, our findings do not support the suggestion that JTC is a transdiagnostic phenomenon beyond psychosis. Highlights: Forty six studies on jumping-to-conclusions bias were included in two meta-analyses. Patients with psychosis had a hastier data-gathering style than healthy controls. JTC is consistently evident in psychotic groups with varied symptom profiles. JTC was not evident in non-psychotic psychiatric disorders after removing outliers. No significant effect of JTC was found in depression.